Interventions to address parenting and parental substance abuse: Conceptual and methodological considerations. (July 2015) - Neger, Emily N.; Prinz, Ronald J.
Abstract: Parental substance abuse is a serious problem affecting the well-being of children and families. The co-occurrence of parental substance abuse and problematic parenting is recognized as a major public health concern. This review focuses on 21 outcome studies that tested dual treatment of substance abuse and parenting. A summary of theoretical conceptualizations of the connections between substance abuse and parenting provides a backdrop for the review. Outcomes of the dual treatment studies were generally positive with respect to reduction of parental substance use and improvement of parenting. Research in this area varied in methodological rigor and needs to overcome challenges regarding design issues, sampling frame, and complexities inherent in such a high-risk population. This area of work can be strengthened by randomized controlled trials, use of mixed-methods outcome measures, consideration of parent involvement with child protective services, involvement of significant others in treatment, provision of concrete supports for treatment attendance and facilitative public policies. Highlights: Parental substance abuse and parenting difficulties dually threaten public health. The nature and quality of dual-treatment outcome studies are reviewed. Multiple pathways and conceptual frameworks inform this area. Methodological rigor varied but positive outcomes were observed. Methodology, interventions, and public policy can and should be strengthened.